The effects of spiritual intelligence and its dimensions on organizational citizenship behaviour - Md. Aftab Anwar; AAhad M. Osman-Gani (Journal of Industrial Engineering and Management (JIEM), 2015)
Purpose: Organizational citizenship behaviour may exist among employees who have inner feelings of having better work experiences by using their spiritual experiences, and also to nurture these by creating meaningful ethical work environments. These phenomena have not been sufficiently studied especially in the context of recent corporate scandals and ethical violations. For this reason, this study seeks to enrich the understanding of relationship of spiritual intelligence and its sub constructs on employee citizenship behaviour among the employees who are working in manufacturing and service organization in Malaysia. Design/methodology/approach: This paper examines the effect of spiritual intelligence and its dimensions on organizational citizenship behaviour among the employees who are working in manufacturing and service industries in Malaysia. Data were collected from 112 employees of the organization from 10 manufacturing and 10 service organization in Peninsular Malaysia. Findings: Multiple regression analyses have revealed that employee spiritual intelligence plays an important role for generating citizenship behaviour among employees. The two important dimensions namely critical existential thinking and transcendental awareness of spiritual intelligence are having great effect on organizational citizenship behaviour. Research limitations/implications: Scholars can develop new research agenda first to identify the nature of effects it might have on employee's performance which can boost the ultimate goal of the organization. Practical implications: Through the finding of this empirical study, it is hoped that it can provide some preliminary assessment and knowledge of the effects of spiritual intelligence of employees and how they relate to the OCB. This would be vital for industrial development by adding relevant policies regarding enhancing employees' OCB. Social implications: This study has the capacity to enhance management awareness concerning recruiting people in terms of spiritual intelligence. People from different culture with high level of citizenship behavior can able to get the job. Originality/value: Organizational management may consider making appropriate decisions for nurturing and developing the relevant dimensions of this intelligence that are lacking among the employees in order to inculcate the spirit of OCB and develop a better work environment. Implications of the research findings for management scholars as well as for management professionals are discussed at the end.
Keywords: 650; spiritual intelligence; organization; citizenship; behavior